2017
DOI: 10.1513/annalsats.201611-918oc
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Hospital Characteristics Associated with Interhospital Transfer for Adults with Ventilator-Dependent Respiratory Failure

Abstract: Rationale: Patients with ventilator-dependent respiratory failure have improved outcomes at centers with greater expertise; yet, most patients are not treated in such facilities. Efforts to align care for respiratory failure and hospital capability would necessarily require interhospital transfer.Objectives: To characterize the prevalence and the patient and hospital factors associated with interhospital transfer of adults residing in Florida with ventilator-dependent respiratory failure.Methods: We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Our prior work evaluating frequency of transfer of ARF patients in Florida showcased a modest transfer rate of 2.9% (10). As a follow-up, in this study, we did observe some variation in transfer frequencies at the state level with the highest rate of transfer observed in Maryland (4.7%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our prior work evaluating frequency of transfer of ARF patients in Florida showcased a modest transfer rate of 2.9% (10). As a follow-up, in this study, we did observe some variation in transfer frequencies at the state level with the highest rate of transfer observed in Maryland (4.7%).…”
Section: Discussionmentioning
confidence: 99%
“…All adult patients 18+ years old with an International Classification of Diseases , 9th and 10th Revision, Clinical Modification (ICD-9 and -10) diagnosis code corresponding to ARF (ICD-9-CM 518.81-.85, ICD-10-CM J96.00-.02), and procedure codes corresponding to mechanical ventilation (ICD-9-procedure code [PCS] 96.70-.72, ICD-10-PCS 5A1935Z, 5A1945Z, 5A1955Z) were identified. We excluded patients whose median LOS at hospital 1 was greater than 25 days as this is indicative of long-term acute care facilities (24, 25), as demonstrated in our prior study (10). In addition, we excluded patients in psychiatric hospitals to obtain our ARF cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive risk factors in addition to neurological deterioration are age and hydrocephalus, among others [ 15 ]. Studies on respiratory disease show lesser likelihood of transfers for patients over 65 years old [ 16 ]. Our study identified that trends in total referrals for migraine, neuro-ophthalmic disease and seizure disorders declined with advancing age but correlated with higher odds of potentially avoidable transfers across all age groups.…”
Section: Discussionmentioning
confidence: 99%